Barriers to Effective Digital Learning Implementation in Madagascar - Marolahy Jacquot Urbain; Paolo Emilio Raholinarivo Solonavalona; Ratianarimamy Niriko Elysa; Marolahy Todisoa Julio Herman (The Nexus Journal of Education, Management, and Entrepreneurship, 2026)
This study aims to examine the key barriers to the effective implementation of digital learning in Madagascar by identifying the structural, institutional, pedagogical, and socio-economic factors that shape digital education practices within a low-income, capacity-constrained education system. The study adopts a qualitative descriptive research design using an interpretive approach. Data are drawn from peer-reviewed academic literature, empirical studies on digital learning and higher education in Madagascar, and comparative evidence from developing and post-crisis education contexts. The analysis applies a thematic analytical technique, involving systematic coding, categorization, and synthesis of recurring patterns related to infrastructure, governance, teacher capacity, access inequality, and technology adoption mechanisms. The findings reveal that the implementation of digital learning in Madagascar is constrained by interconnected barriers, including inadequate digital and physical infrastructure, limited institutional and governance capacity, insufficient teacher digital competence, and persistent socio-economic inequality that affects access and participation. Advanced technologies such as artificial intelligence offer potential benefits, yet their effectiveness remains limited by unresolved foundational conditions, and their adoption could exacerbate existing disparities if implemented prematurely. This study contributes original value by providing a context-sensitive and integrative analysis of digital learning barriers in Madagascar, moving beyond technology-centered explanations. By linking digital transformation theory with empirical evidence from a structurally constrained education system, the study offers practical insights for policy design and institutional reform. It enriches the literature on the implementation of digital education in low-income and developing contexts.